2013
DOI: 10.1111/sdi.12069
|View full text |Cite
|
Sign up to set email alerts
|

What Nephrologists Need to Know about Vascular Access Cannulation

Abstract: This article describes cannulation events, especially problems, common and rare, minor and major, to aid the nephrologist (and mid-level providers e.g. nurse practitioner and physician's assistant) in decision-making to prevent or treat cannulation-related adverse outcomes. The usual management, potential outcomes, nephrologist intervention, and prevention are discussed and include: assessment of arteriovenous (AV) access and readiness for cannulation; initial cannulation of both arteriovenous fistulas and gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 24 publications
(42 reference statements)
0
39
0
Order By: Relevance
“…11,12 Thus, in the data analysis, the third consecutive cannulation was considered the marker for the end of catheter-dependent dialysis, even though some TDCs may have remained in place awaiting orders for or scheduling of removal.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 Thus, in the data analysis, the third consecutive cannulation was considered the marker for the end of catheter-dependent dialysis, even though some TDCs may have remained in place awaiting orders for or scheduling of removal.…”
Section: Methodsmentioning
confidence: 99%
“…We also found that those using needles with larger diameter tended to rate Mutsu-Senshi® more favorably, and this factor was significant even in the multivariate regression analysis. Needle insertion pain is a considerable stress for patients receiving HD [4,5]. It may be associated with depressive symptoms and lower quality of life in patients with HD [19].…”
Section: Discussionmentioning
confidence: 99%
“…Pain associated with the insertion of dialysis needles can cause considerable stress on HD patients [4]. In fact, pain during needle insertion is the most common patient complaint regarding hemodialysis access [5].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular access (VA) complications have been attributed to inadequate assessment, inappropriate cannulation practices and complications remaining undetected (Dinwiddie et al . ). Regular monitoring by skilled nephrologists and nurses utilising physical examinations is the cornerstone of VA surveillance programmes however, VA surveillance is the responsibility of everyone involved in the patient's VA care, which can include the patient and carer (Feddersen & Roger ).…”
Section: Introductionmentioning
confidence: 97%
“…Godbold (2013) defined carers as the patient's relative or friend whose role includes supporting the patient at home and or accompany them to haemodialysis therapy sessions, clinics and hospital. and complications remaining undetected (Dinwiddie et al 2013). Regular monitoring by skilled nephrologists and nurses utilising physical examinations is the cornerstone of VA surveillance programmes however, VA surveillance is the responsibility of everyone involved in the patient's VA care, which can include the patient and carer (Feddersen & Roger 2012).…”
Section: Introductionmentioning
confidence: 99%